QUEERING THE MAP: PHYSICAL TRACES AND DIGITAL PLACES OF QUEER LIVES - Robards, Brady; Watson, Ashleigh; Kirby, Emma; Churchill, Brendan; LaRochelle, Lucas (AoIR Selected Papers of Internet Research, 2020)
QueeringTheMap.com, launched in late 2017 by designer Lucas LaRochelle, is a ‘community-generated mapping project that geo-locates queer moments, memories and histories in relation to physical space’. In a Google Maps-style interface, users can locate pins anchored to physical locations. Attached to each pin is a story. Collectively, there are tens of thousands of stories about being lesbian, gay, bisexual, transgender, non-binary, and gender non-conforming: coming out stories, stories of first kisses, sexual encounters, break-ups, pride marches, assaults, traumas, and realisations. These stories digitally layer physical spaces with anonymous individual and collective stories; they locate queer life and they queer the map. In this project we seek to document these experiences, improve understandings of community archiving and digital storytelling practices, and expose the potential for reconfiguring forms of resistance and solidarity through new platforms for collectivity and community-making. In this paper, we consider how these narratives may be understood at scale to provide insights into the digital architecture of queer lives. We focus our analysis on the 1,941 posts pinned to Australia, to consider how QTM reaffirms contemporary understandings of the physical-digital continuum and queers how we conceive of traces and places in this context.